Debt Build-up in Frontier Low-Income Developing Countries (LIDCs) since 2012 : Global or Country-specific Factors and Way Forward? - de Soyres, Constance; Rogantini Picco, Anna.; Sab, Randa (Washington, D.C. : International Monetary Fund, 2019)
This paper focuses on the debt build-up that frontier low-income developing countries (LIDCs) have faced since 2012. First, it documents a 20-percentage point increase in the external and government debt-to-GDP ratios, a composition shift toward higher non-concessional debt, and a rise in interest rate payments. Second, using panel regressions, it shows that while both global and country-specific factors are correlated with debt-to-GDP ratios over 1998-2016, global factors dominate for the period 2012-16. Third, through a small open-economy model, it shows that the projected tightening in global financial conditions would reduce debt-to-GDP ratios by less than the increase associated with the expected rise in investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet